Cellular compartment model for exploring the effect of the lipidic membrane on the kinetics of encapsulated biochemical reactions - Sunami, Takeshi (Langmuir : the ACS journal of surfaces and colloids, 2010)
One of the important characteristics of the cellular system is that interactions between the plasma membrane and water-soluble molecules in the cytoplasm are enhanced by the confinement of the molecules to the small volume of the intracellular space. Studying this effect in a model cell system, we measured the time evolution of an enzymatic hydrolysis reaction and a cell-free protein synthesis reaction taking place in giant liposomes having various size and phospholipid compositions by a flow cytometry. This single vesicle-based assay of a large number of liposomes enabled us to examine the volume dependence of enclosed reactions in detail, revealing that the presence of specific lipid affected the specific kinetic parameters of encapsulated reactions